Biological and orthodontic treatment risk factors associated to external root resorption: a case-control study - Sonia Patricia Plaza-Ruíz (Universidad de Antioquia, 2020)
Introduction: external apical root resorption (EARR) is considered an adverse effect related to orthodontic treatment, but its specific risk factors remain controversial. The aim of this study was to identify the biological and orthodontic treatment risk factors associated with EARR in the incisors of patients who completed orthodontic treatment. Method: case-control study. 126 subjects (27.81 + 11.02 years old; 56 men, 70 women) selected for convenience; 63 cases and 63 controls, matched with cases in age and sex. EARR was measured on panoramic radiographs using the Levander and Malmgren classification. Demographic, biological, and orthodontic treatment-related variables were taken from clinical records. The cephalometric variables before and after treatment were measured with the Dolphin software. Statistical analysis included: Chi2, U Mann Whitney, t-test, and logistic regression models. Statistical significance was established at p<0.05. Results: there was evidence of association between EARR and previous root resorption (p=0.028; OR=24.925; 95% CI 1.427; 435.344); horizontal skeletal pattern (p=0.008, OR=0.914, 95% CI:0.854;0.977); pre-treatment upper incisor position (p=0.023; OR=0.850; 95% CI:0.738;0.978) and pre-treatment lower incisor position (p=0.019; OR=0.838; 95% CI:0.724;0.971). Previous root resorption and vertical skeletal pattern were significantly associated with EARR in the final multiple regression model. Conclusions: radiographic controland adaptation of orthodontic treatment is recommended in subjects who have previous root resorption and a horizontal skeletal pattern, since they are more likely to present EARR.